A Meta-analysis: Therapeutic Effect of Tai Chi on Low Back Pain - Xiang LI; Xiangbin WANG; Tianjiao LI; Jian HE; Meijin HOU (康复学报)
Objective:To systematically review the therapeutic effect of Tai Chi on low back pain.Methods:We searched NCBI, CNKI, WanFang Data and VIP databases to collect randomized controlled trials (RCTs) about Tai Chi exercise on low back pain, and the search period was from January 2000 to December 2016. Two reviewers independently screened literature, extracted data and assessed the risk of bias of included studies. Meta-analysis was performed by using RevMan 5.3 software.Results:A total of 327 related articles were retrieved and six articles were included. Pain numerical rating scale (NRS) score of the Tai Chi exercise group was significantly lower than that of control group [MD=-3.11, 95%CI (-3.40, -2.82), P<0.01], Roland-Morris Disability Questionnaire (RMDQ) score of functional activity was significantly decreased [MD=-0.84, 95%CI (-1.05, -0.63), P<0.01].Conclusion:Tai Chi exercise can reduce subjective feelings of pain in patients with low back pain, improve daily function of patients with a variety of activities. Above conclusions still depend on large sample, multi-center, high-quality RCT to verify.